2019
DOI: 10.1186/s40580-019-0195-0
|View full text |Cite
|
Sign up to set email alerts
|

Design and applications of stretchable and self-healable conductors for soft electronics

Abstract: Soft and conformable electronics are emerging rapidly and is envisioned as the future of next-generation electronic devices where devices can be readily deployed in various environments, such as on-body, on-skin or as a biomedical implant. Modern day electronics require electrical conductors as the fundamental building block for stretchable electronic devices and systems. In this review, we will study the various strategies and methods of designing and fabricating materials which are conductive, stretchable an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 189 publications
(231 reference statements)
0
50
0
1
Order By: Relevance
“…Furthermore, innovative chemistries and processing techniques will enable the development of sustainable and fully biodegradable electronic devices that would degrade once no longer needed [245,246] or would self-recover after being damaged. [247][248][249] CPs, coupled with natural/common-commodity products, are promising candidates for the development of biodegradable-ingestible electronics, as edible diagnostic and therapeutic tools and food-distribution chain electronic tags. [250,251] In the coming new era, biodegradable electronic materials will be a necessity, where benign integration of our devices into the environment will be crucial.…”
Section: Outlook and Road Mapmentioning
confidence: 99%
“…Furthermore, innovative chemistries and processing techniques will enable the development of sustainable and fully biodegradable electronic devices that would degrade once no longer needed [245,246] or would self-recover after being damaged. [247][248][249] CPs, coupled with natural/common-commodity products, are promising candidates for the development of biodegradable-ingestible electronics, as edible diagnostic and therapeutic tools and food-distribution chain electronic tags. [250,251] In the coming new era, biodegradable electronic materials will be a necessity, where benign integration of our devices into the environment will be crucial.…”
Section: Outlook and Road Mapmentioning
confidence: 99%
“…Such characteristics enable stable percolation of nanomaterials even under deformation, resulting in high stretchability. [84,85] As an example, Kim et al have shown the strain-induced self-organization of NPs in the elastomeric matrix and analyzed its effect on the performance of nanocomposites. [86] When strain is applied to a nanocomposite composed of PU and Au NPs, the percolation network of Au NPs rearranges, mainly following the stretched direction (Figure 6a).…”
Section: Controlled Percolation Of Nanomaterialsmentioning
confidence: 99%
“…When the nanocomposite is elongated, the percolation network of nanomaterials rearranges in response to the applied strain, and this rearrangement deforms the shape of the network and protects the connection of network from fracture. Such characteristics enable stable percolation of nanomaterials even under deformation, resulting in high stretchability …”
Section: Approaches To Maximize Stretchability Of the Nanocompositementioning
confidence: 99%
“…Moreover, they should be comfortable for the users and can be easily incorporated into clothing. However, in [ 175 ], polymer materials have received considerable attention due to their unique electrical and mechanical properties and are easily incorporated into various high-performance conducting and substrate materials, such as zirconia ceramic, liquid crystal, or liquid metals, and different composite materials, like MXene ink, etc. Table 4 shows the properties of various flexible materials.…”
Section: Flexible Materialsmentioning
confidence: 99%